Male management and female management: pending reflections - Alcaide-Aranda, Lourdes Ivonne del Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
It is essential to strengthen the path towards greater participation and democratic expansion; however, gender is still considered a marker of difference. With a multi-case, Kicross-sectional study with a mixed methodological approach, it was concluded that managers tend to stereotype their own behavior according to the cultural values conceived by society for each sex and that the further development of management practice, principles of male direction according to Mintzberg and/or female direction according to Helgesen in order to propose improvement guidelines, it may be due to the emphasis placed by each director.